2021
DOI: 10.30722/anzjes.vol12.iss3.15359
|View full text |Cite
|
Sign up to set email alerts
|

Facing a ‘civilisational choice’: Images of Europe by the populist radical right in the 2019 European elections

Abstract: This paper deals with the perceptions of Europe as developed by the European populist radical right over the campaign for the 2019 European Parliament elections. The study is based on the public communications of three leading political parties in this spectrum: France’s Rassemblement national, Italy’s Lega and Germany’s Alternative für Deutschland. By applying image theory in international relations, the paper comes to the conclusion that the radical right managed to construct a relatively coherent image of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…argue neoliberalism is a set of ideas and actions whose objective is to restore, expand and maintain the power of economic elites relative to ordinary people. This idea feeds into traditional populist divisions of "us V them" and "the elite V the people" and fuels the narrative of "Bureaucratic Brussels" handing power to the unelected representatives of the European Commission (EC) and away from the people (Popivanov, 2020). Political and economic elites responded to the GFC with self-interest at the expense of the people to ensure they maintained their power, status and wealth in society .…”
Section: The Link Between Neoliberalism and Nationalismmentioning
confidence: 99%
See 4 more Smart Citations
“…argue neoliberalism is a set of ideas and actions whose objective is to restore, expand and maintain the power of economic elites relative to ordinary people. This idea feeds into traditional populist divisions of "us V them" and "the elite V the people" and fuels the narrative of "Bureaucratic Brussels" handing power to the unelected representatives of the European Commission (EC) and away from the people (Popivanov, 2020). Political and economic elites responded to the GFC with self-interest at the expense of the people to ensure they maintained their power, status and wealth in society .…”
Section: The Link Between Neoliberalism and Nationalismmentioning
confidence: 99%
“…Their research into voter perceptions showed that people who disapproved of the EU performance in the crisis, were more likely to vote for a hard-Eurosceptic party in the 2014 European Parliamentary (EP) elections. The EP elections of 2014 (Mascitelli, 2018) and 2019 (Popivanov, 2020) have been viewed as pivotal in the development of European integration. The results marked an advancement and subsequent consolidation of radical populist and right-wing nationalist representation in the EP.…”
Section: The Link Between Neoliberalism and Nationalismmentioning
confidence: 99%
See 3 more Smart Citations